FRAUD DIAMOND ANALYSIS IN DETECTING FRAUDULENT FINANCIAL STATEMENT - Annisa Nurbaiti; Nuraini Suatkab (Jurnal Manajemen Indonesia, 2019)
Fraudulent financial statement is the least common fraud but has the greatest loss of impact compared to other types of fraud. This certainly can make mistakes in terms of decision making. This study aims to analyze fraudulent financial statements in the perspective of diamond fraud in the form of pressure, opportunity, rationalization, and capability. The number of samples is 175 consisting of 35 property, real estate and building construction companies listed on the Indonesia Stock Exchange in 2013-2017. The results showed that financial stability, external pressure, financial targets, the nature of industry, ineffective monitoring, change in auditors, audit opinion, change in director simultaneously influence the fraudulent financial statement. Partially, financial targets, nature of industry, ineffective monitoring has a significant positive effect on fraudulent financial statements while financial stability, external pressure, change in auditors, audit opinions, and change in director have no effect on fraudulent financial statements. Keywords—Pressure, Opportunity, Rationalization, Capability, Fraudulent Financial Statement. AbstrakKecurangan laporan keuangan merupakan kecurangan yang paling jarang terjadi namun memiliki dampak kerugian yang paling besar dibanding jenis kecurangan lainnya. Hal ini tentu dapat membuat kekeliruan dalam hal pengambilan keputusan. Penelitian ini bertujuan menganalisis fraudulent financial statement dalam perspektif fraud diamond berupa pressure, opportunity, rationalization, dan capability. Teknik purposive sampling merupakan teknik pengambilan sampel yang digunakan, dimana diperoleh 175 sampel yang terdiri dari 35 perusahaan properti, real estate, dan konstruksi bangunan yang terdaftar di BEI tahun 2013-2017. Analisis regresi data panel merupakan metode analisis yang digunakan dalam penelitian ini dengan menggunakan software berupa EVIEWS 9. Lebih lanjut, hasil penelitian menunjukkan bahwa secara simultan variabel independen yakni financial target, external pressure, financial stability, nature of industry, ketidakefektifan pengawasan, change in auditor, audit opinion, change in director berpengaruh terhadap fraudulent financial statement. Sedangkan secara parsial, variabel financial target, nature of industry, ketidakefektifan pengawasan memiliki pengaruh positif signifikan terhadap fraudulent financial statement dan untuk variabel external pressure, financial stability, change in auditor, audit opinion, dan change in director tidak memiliki pengaruh terhadap fraudulent financial statement. Kata Kunci—Pressure, Opportunity, Rationalization, Capability, Fraudulent Financial Statement.ement